OPTIMALISASI PERAN GURU DALAM PROSES PEMBELAJARAN KURIKULUM 2013 DI MADRASAH IBTIDAIYAH SWASTA - Sri Endang Puji Astuti; Aslan Aslan; Parni Parni (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Kediri, 2023)
This paper aims to analyze the teacher's role in the 2013 curriculum-based learning process in private Islamic elementary schools. The research method used in this study was descriptive qualitative. The data collection method used consisted of interviews, observation, and documentation. The results of this study found that there were five teacher roles; educator and teacher, mediator, motivator, role model, mentor and evaluator. These five roles were a positive impact of the role of the madrasah principal, who encourages teachers to be actively involved in the teachers' work group (KKG) and regular meetings before the implementation of learning begins each semester. In the learning process in the classroom, the five teacher roles are intertwined into a unit so that the learning process can proceed according to the stages of implementing the 2013 curriculum and using a scientific approach.